Analisis Literatur Sistematik Terhadap Penentuan Agihan Bantuan Kemiskinan Kepada Golongan B40 Di Malaysia - Azman Ab Rahman; Afaf Sukari; Muhammad Faiz Abd. Shakor; Syed Salim Syed Shamsuddin; Zizi Azlinda Mohd Yusof (USIM Press, 2024)
VOL. 28 NO. 2 Page (70-86)